Apocalyptic thinking in early Judaism: engaging with John Collins' "The Apocalyptic imagination" - Crawford, Sidnie White; Wassen, Cecilia (Journal for the study of Judaism, 2018)
Front Matter -- Copyright page -- Contributors -- Introduction /Sidnie White Crawford and Cecilia Wassén -- The Apocalypse and the Sage: Assessing the Contribution of John J. Collins to the Study of Apocalypticism /Matthew Goff -- A Dwelling Place of Demons: Demonology and Apocalypticism in the Dead Sea Scrolls /Bennie H. Reynolds III -- End Time Temples in the Dead Sea Scrolls: Expectations and Conflict /Cecilia Wassén -- Situating the Aramaic Texts from Qumran: Reconsidering Their Language and Socio-Historical Settings1 /Daniel Machiela -- The Aramaic Imagination: Incubating Apocalyptic Thought and Genre in Dream-Visions among the Qumran Aramaic Texts1 /Andrew B. Perrin -- Origins of Evil in Genesis and the Apocalyptic Traditions /Ida Fröhlich -- Eschatology and Time in 1 Enoch /Loren Stuckenbruck -- The Ram and Qumran: The Eschatological Character of the Ram in the Animal Apocalypse (1 En. 90:10–13) /Eyal Regev -- Comparative Eschatology: Paul’s Letters and the Dead Sea Scrolls1 /Adela Yarbro Collins -- The End is Not Yet: Concluding Reflections /John J. Collins.